HUBUNGAN PICKY EATING DENGAN KEJADIAN STUNTING PADA ANAK PRASEKOLAH DI TKA NURUL HUDA TUMARITIS KABUPATEN BOGOR - Parida Pebruanti (2021)
Stunting or also called short body is defined as a condition of failure of child growth caused by lack of nutrient intake for a very long time due to low nutritional needs that enter the body. One of the causes of stunted growth in children can be influenced by picky eating behavior. Picky eating has the characteristics of being picky eaters, refusing food and only liking the food they choose, this if left unchecked the child will have the potential to experience a lack of nutritional intake that can affect the growth process. This study was conducted to analyze the relationship between picky eating and the incidence of stunting in preschool children at TKA Nurul Huda Tumaritis, Bogor Regency. The method used is descriptive quantitative with cross sectional design. Sampling of the study used a total sampling of 73 mothers and their children. Data was collected through a questionnaire containing demographic and picky eating data determined using the CEBQ (Children Eating Behavior Questionnaire) scale, as well as measuring children's height. The results of the analysis using the chi-square test obtained a p value = 0.023 (p <0.05), which means that there is a relationship between picky eating and the incidence of stunting in preschool children at TKA Nurul Huda Tumaritis, Bogor Regency. Suggestions for further research to carry out research with a wider population.